PENGARUH CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK (Studi Kasus Pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2015-2018) - Satriawaty Migang; Winda Rivia Dina (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2020)
ABSTRACT This study aims to examine the effect of corporate governance and disclosure of corporate social responsibility on the tax aggressiveness of mining companies listed on the Indonesia Stock Exchange in 2015-2018. This study uses 8 sample companies from 38 populations. Tax aggressiveness is proxied using ETR, corporate governance is proxied using independent commissioners, audit committees, and institutional ownership. Corporate social responsibility is measured using CSR disclosure indicators based on the Global Reporting Initiative (GRI) guidelines. The results of this study indicate that corporate governance that is proxied by using independent commissioners and institutional ownership also corporate social responsibility has an effect on tax aggressiveness, while corporate governance that is proxied using audit committees does not affect tax aggressiveness. Keywords: tax aggressiveness, corporate governance, corporate social responsibility.